Le plan de gestion patrimoniale : un outil de gestion pour les grands ensembles protégés - Anne Van Loo (In Situ)
Most of the time, the dimensions of outstanding built housing estates are an obstacle to their protection because of the resulting obligations for their owners (who must comply with constraining procedures) as well as for authorities (which make financial contribution to their maintenance). However, the very composition of these architectural ensembles, the repetition of their shapes and materials offer the answers to a reasoned approach to their future, so that they continue to be ensembles and do not develop on a case by case basis. The heritage management plan (HMP) of the garden cities of Le Logis and Floréal in Brussels exploits the characteristics of these two ensembles (1600 dwellings) to specify the manner in which components were originally designed, how they interact with each other and how they should be maintained to ensure the longevity of it all. It is possible to deviate from the HMP. Nevertheless, the administrative procedures simplification and financial supports resulting from the compliance with them act as encouragement to adopt the rules. Implemented from 2001, the HMP was supplemented in 2014, mainly by construction recommendations, requirements and details relating to sanitary conditions and comfort of housing to meet the new energy concerns. After twenty years or so of implementation, we can observe that the urban and architectural coherence of the garden cities has been preserved while ensuring the conservation of the original buildings.